2008
DOI: 10.1007/s10038-008-0304-0
|View full text |Cite
|
Sign up to set email alerts
|

Association study of the C3 gene with adult and childhood asthma

Abstract: Bronchial asthma (BA) is a multifactorial disorder, the development of which is affected by both environmental and genetic factors. The complement system plays an important role in immunological response against invading microorganisms. It has been shown that complement-C3-deficient mice have reduced inflammation of asthmatic airways. Previously, we reported the association of four single nuclear proteins (SNPs) in the exons of the C3 gene with childhood and adult BA. The C3 gene, however, is a large gene, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Like CNV, BA is a multifunctional disorder with both environmental and genetic factors contributing to its development. Recent studies reveal that the complement system plays a crucial role in the development of immunological responses in BA by initiating and/or amplifying airway inflammation [16], [17]. Variations of genes in the complement system have been shown to confer susceptibility to BA, including complement factor 3(C3) and complement factor 4(C4).…”
Section: Introductionmentioning
confidence: 99%
“…Like CNV, BA is a multifunctional disorder with both environmental and genetic factors contributing to its development. Recent studies reveal that the complement system plays a crucial role in the development of immunological responses in BA by initiating and/or amplifying airway inflammation [16], [17]. Variations of genes in the complement system have been shown to confer susceptibility to BA, including complement factor 3(C3) and complement factor 4(C4).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the mechanism of this association remains uncertain, it should be noted that a similar genetic interval, incorporating intron 27, has also been associated with bronchial asthma, adding additional weight to our argument that non-coding variation in the central region of C3 is a true disease susceptibility effect. 17 It is important to compare our results with the only other study, in a Japanese population, to also report association between C3 polymorphisms and both serum C3 and SLE. 10 There are notable differences between the variants found to be associated with SLE.…”
Section: Discussionmentioning
confidence: 73%
“…One study demonstrated significant associations with wheezing in the 15 months after RSV LRI ( IL19, IL20, MUC5AC, TNFRSF1B, C3, CTLA4, CXCL9, IL4R and IL7 ) [124], of which C3, CTLA4 and IL4R overlap with variants identified with asthma [125129]. They also identified a functional SNP in IL13 associated with 6-year wheezing outcomes (n = 72) after RSV LRI [130], which has replicated inconsistently in studies of asthma [125].…”
Section: Status Of Current Genetic Knowledge On Shared Genes For Rsv mentioning
confidence: 99%